Correlation between bruxism and pain of endodontic origin: a case report (Research, Society and Development, 2020)
The objective was to report a case of endodontic treatment in a patient diagnosed with irreversible pulpitis presenting as a causative and aggravating factor severe bruxism. Patient G. L. A., a 55-year-old, military police officer, attended the clinic complaining of “toothache”, characterized by being localized, of long duration, moderate intensity and caused by thermal and masticatory stimuli. During the anamnesis, the patient reported to be allergic to dipyrone sodium and hypertensive, making use of Captopril®. During the intra-oral physical examination, was observed that the complaint was regarding the element 34, which did not present fistula. The patient had a history of severe bruxism, presenting extensive occlusal wear of all the dental elements and made use of a myorelaxing plate. Percussion and pulpar vitality tests were performed, reaching a final diagnosis of irreversible pulpitis, making it necessary to perform conventional pulpectomy as treatment. The endodontic treatment performed successfully attended the patient’s needs, starting with the pain relief and, so that the stomatognathic system could also be restored, he was referred to the clinic for oral rehabilitation.